SOLO MEGA SINEPLEKS SEBAGAI WADAH APRESIASI PERFILMAN YANG EDUKATIF DAN REKREATIF - Febriar Nilamsari; Hardiyati Hardiyati; Muhammad Asrori (Universitas Sebelas Maret Surakarta, 2015)
Film is one of the entertainment media that can be used as a medium of learning. Currently, film is developing in Indonesia, as well as in Surakarta. Many people, especially young people to appreciate the film. They watch movies and many are keen to make it. The aims of Solo Mega Sinepleks were to facilitate cinema activities that entertain and contains elements of education, including watching movies and filmmaking learning. The problem is how to realize interesting building, can incorporate elements of education and recreation, full filling cineplex and its supporting facility standard, and achieve the look of the building that could represent the function inside. The method is by processing of exterior appearance and layout inside the building to create a cineplex which facilitate educational activities with recreational design. Results obtained in the form of building design that is able to represent the function of the building as an educational film center with an attractive design and convenient for visitors. Keywords: Cineplex, Educative, Film Appreciation, Recreational